2005
DOI: 10.1124/jpet.105.086835
|View full text |Cite
|
Sign up to set email alerts
|

Increased Potency of a Novel Complement Factor 5a Receptor Antagonist in a Rat Model of Inflammatory Bowel Disease

Abstract: We have previously shown that complement factor 5a (C5a) plays a role in the pathogenesis of 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis in rats by using the selective,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 26 publications
2
78
0
1
Order By: Relevance
“…We have previously shown that PMX205 reduces C5a-mediated pathology in several inflammatory models (25), including an acute model of Huntington's disease (18). The present study provides compelling evidence that the complement system and, in particular C5a, is involved in the disease progression seen in our rat model of ALS.…”
Section: Treatment With a C5ar Antagonist Extends Survival Times And supporting
confidence: 56%
See 2 more Smart Citations
“…We have previously shown that PMX205 reduces C5a-mediated pathology in several inflammatory models (25), including an acute model of Huntington's disease (18). The present study provides compelling evidence that the complement system and, in particular C5a, is involved in the disease progression seen in our rat model of ALS.…”
Section: Treatment With a C5ar Antagonist Extends Survival Times And supporting
confidence: 56%
“…This orally active compound (25) crosses the blood-brain barrier and has been shown to have a protective effect in an acute model of striatal degeneration (18). Furthermore, PMX205 displays little detectable affinity for C5L2 (36).…”
Section: Treatment With a C5ar Antagonist Extends Survival Times And mentioning
confidence: 99%
See 1 more Smart Citation
“…PMX-53 is a peptidic C5aR antagonist and has proven to be advantageous in experimental animal studies for neurodegenerative diseases, rheumatoid arthritis, ischemia/reperfusion and inflammatory bowel disease (102,166,167). It is currently being evaluated in clinical trials, but a recent study in humans failed to show significant effects on synovial inflammation (168).…”
Section: Immunomodulation Of Complementmentioning
confidence: 99%
“…It was reported that C5a contributed to the initiation and/or amplification of various pathological conditions such as ischemia-reperfusion injury, inflammatory bowel disease, arthritis, antiglomerular basement membrane nephritis, septic shock, Alzheimer's disease, and hemodialysis in animal models and humans (1,5,7,14,16,27,40,41,44) Therefore, C5a might be a target as an anti-C therapy as a way to prevent inflammatory tissue injury. There are numerous agents for inhibition of C5a, such as C5aR antagonists (C5aRA) and monoclonal anti-C5a IgG (10,28,42).…”
mentioning
confidence: 99%